Spirituality of the Soul and the Human Person according to the Carmelite Mystics. - Niziński, Sergiusz (Filozofia Chrześcijańska, 2010)
While speaking of the deepest experience of God, some Christian mystics mention that it takes place within the essence of the soul or within its centre, which is sometimes called spirit. Since a soul does not have parts, spirit is a counterpart of some specific „acting" of a soul which consists in passive opening towards God's action. Man experiences God in spirit. Such experience is something more than faith in God's presence within us. In spirit man feels God's presence. For Carmelite mystics, such moments are man's highest personal acts. Therefore one can say that a person fully expresses oneself just in this passive capability to open to this contact with God. Hence one can state that a person is a soul in a dimension of acting independently of the matter and in the dimension of giving oneself and receiving the other person.